Aislamiento, identificación y caracterización de hongos nematófagos depredadores nativos de Costa Rica - Orozco Aceves, Martha (2015)
Tropical ecosystems provide biological resources with potential to be used in agricultu- re, for example, the predatory nematophagous fungi (PNF), which can be used as biological control agents of parasitic nematodes of plants and animals. A successful biological control should incorpo- rate locally isolated organisms, for this reason the aim of this study was to investigate the presence of PNF in non-disturbed ecosystems and agroecosystems of Costa Rica. Samples of soil, litter, organic fertilizers, and animal feces were collected across five counties of Costa Rica, and screened for PNF through the soil sprinkling technique. Twenty-seven strains were isolated; 15 Candelabrella musiformis, 11 Arthrobotrys oligospora, and one Dactylella sp. The strains were morphologically characterized both macro and microscopically. Our results indicated that strains of PNF are locally available in Costa Rica, therefore their use as part of a biological control strategy to combat parasitic nematodes is viable.